Practical responses to confidentiality dilemmas in elite sport medicine. Issue 19 (23rd July 2013) - Malcolm, Dominic; Scott, Andrea
Abstract : Aim: To examine the ethical challenges of upholding patient confidentiality in sports medicine and the practical responses of clinicians to these challenges. Method: Questionnaire survey and follow-up semi-structured interviews with the members of the British Olympic Association's Medical Committee and Physiotherapy Forum. Results: Clinicians identified three contextual factors that influenced issues related to patient confidentiality in sports medicine: the use of confidentiality waivers; the facilities available for treatment; and the cultural norms of elite sport. They further identified interpersonal strategies used to lessen or eradicate conflicts, including emphasising the benefits and avoidance of disbenefits for athletes and the potential negative consequences for others. Conclusions: Aspects of clinicians' practice environment should be designed to enable compliance with the highest levels of ethical conduct. Professional associations should establish guidelines for clinicians' interpersonal conduct in dealing with confidentiality issues and consider their provision of ethics-based continuous professional development. They should also petition for the establishment of athletes' codes of conduct which identify a context-relevant understanding of 'serious harm' and how that might impact on information disclosure.